Islamic Law and Finance : Religion, Risk, and Return - Mallat, Chibli, (Arab and Islamic Laws Series ;, 1988)
Since banking and financial industries in countries observing Islamic law and the Shari'a are growing fast, it is essential for the West to obtain a better understanding of the interaction between Islamic law and finance. As all financial business is bound by the Shari'a, western lawyers and economists must consider the extent to which flexibility exists in the western system whereby the two systems, western and Islamic, can be brought closer together. This book presents a collection of papers from distinguishesd authors analysing the various attempts to establish a system of Islamic law and finance and it investigates the modes of operations of institutions adopting the Islamic system, drawing on examples such as Malaysia, Iran and Pakistan, ans Egypt - all of which are international and cover a large economically significant area of operations, laws and taxation systems. See Less